2021
DOI: 10.3847/psj/ac1ce6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tidal Obliquity Variations with SMERCURY-T

Abstract: We introduce our new code, SMERCURY-T, which is based on existing codes SMERCURY and Mercury-T. The result is a mixed-variable symplectic N-body integrator that can compute the orbital and spin evolution of a planet within a multiplanet system under the influence of tidal spin torques from its star. We validate our implementation by comparing our experimental results to that of a secular model. As we demonstrate in a series of experiments, SMERCURY-T allows for the study of secular spin–orbit resonance crossin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…They used this code to draw insights regarding the habitability of the Kepler-62 system (Borucki et al 2013) and showed the two planets in the system's habitable zone are likely to differ greatly in both obliquity and spin rate, with natural consequences for their habitability. Kreyche et al (2021) expanded on this framework with SMERCURY-T, providing a framework that can selfconsistently track the orbit and spin evolution of bodies in a multiplanet system under tidal influences from all bodies. Chen et al (2021) presented their independent consistent symplectic integrator package as well, GRIT.…”
Section: Introductionmentioning
confidence: 99%
“…They used this code to draw insights regarding the habitability of the Kepler-62 system (Borucki et al 2013) and showed the two planets in the system's habitable zone are likely to differ greatly in both obliquity and spin rate, with natural consequences for their habitability. Kreyche et al (2021) expanded on this framework with SMERCURY-T, providing a framework that can selfconsistently track the orbit and spin evolution of bodies in a multiplanet system under tidal influences from all bodies. Chen et al (2021) presented their independent consistent symplectic integrator package as well, GRIT.…”
Section: Introductionmentioning
confidence: 99%